2013
DOI: 10.1007/s10936-013-9257-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilingualism and Trilingualism in L2 Production: Evidence from Errors and Self-Repairs in Early Balanced Bilingual and Trilingual Adults

Abstract: Through analyzing response latencies, errors, and self-repairs in Mandarin, this investigation explores how monolingual, bilingual, and trilingual adults process their speech production differently using cognitive control mechanisms. In this study we conducted two experiments involving speech production in Mandarin. In the two experiments, 81 adults participated and were categorized into three groups: Mandarin monolingual, Hakka-Mandarin bilingual, and Hakka-Mandarin-Minnan trilingual. In Experiment 1 (unprepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Of the 56, 46 were original studies [7,14,21,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] and 10 were review/meta-analysis studies [70,71,72,73,74,75,76,77,78,79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14,21,27,29,30,31,32,34,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 56, 46 were original studies [7,14,21,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] and 10 were review/meta-analysis studies [70,71,72,73,74,75,76,77,78,79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14,21,27,29,30,31,32,34,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…Monolingual, bilingual, and trilingual participants were tested in that study. Hsu [44] found that for the trilingual participants, a clear advantage in inhibitory and attentional control existed while for the bilingual participants only an advantage in inhibitory control was found when compared to the monolinguals. In a recent study by Hsu [61], balanced and unbalanced bilinguals were found to be better than the monolinguals on the non-contextual single-character reading task (regardless of their first language background), but not on the contextual multi-word task.…”
Section: Behavioral Resultsmentioning
confidence: 97%
“…Of the 56, 46 were original studies [7,14,21,, and 10 were review/meta-analysis studies [70][71][72][73][74][75][76][77][78][79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14, 21, 27, 29-32, 34, 38, 45, 48, 53-55, 60, 63, 69-72, 74, 75, 78], 5 (8.9%) having been conducted by a North American/European collaboration [36,42,47,50,58], 2 (3.6%) having been conducted by a North American/Asian collaboration [54,61], 1 (1.8%) having been conducted by a North American/European/Asian collaboration [28], 18 (32.1%) having been European studies [33, 35, 37, 39, 41, 43, 46, 49, 51, 52, 57, 64, 66-68, 73, 76, 77], 1 (1.8%) having been conducted by an European/Australian collaboration [40], 2 (3.6%) having been conducted by an European/Asian collaboration [7,79], and 4 (7.1%) having been Asian studies [44,59,61,65]. To date, of 28 African or Latin American studies on bilingualism and cognitive control still have not been published.…”
Section: General Resultsmentioning
confidence: 99%
See 2 more Smart Citations